Research and Application of Voice Technology in Mine Transport Vehicles - LIU Yue; LUO Xiao; CHU Wei; CHEN Jingxian; LIU Ren (Kongzhi Yu Xinxi Jishu)
In order to develop more intelligent transport vehicles for surface mines to enable the drivers work more efficiently and safely, this paper puts forward a solution of applying voice technology to the cab of mine transport vehicle and ground command center. This approach encompasses an array of functions, including noise reduction based on array microphone pickup, voice wake-up, speech recognition, and speech synthesis. Relying on the on-board display platform and ground server platform, two modules were developed respectively for voice interaction and voice broadcasting, to enable keyword recognition and emergency broadcasting of dangerous situations. According to the results of laboratory test and field test at mines, the application of this solution managed to meet the echo suppression effect of 20 dB reduction in the cab, and control the bottom noise of spectrograms within 200-300 sample, meeting the subsequent demand for audio quality recognition; the model demonstrated a recognition accuracy greater than 85% and a real-time rate less than 500 ms, in the normal on-board environment and at a pickup distance of 80 cm. The results verifies that the functions and performances of the voice noise reduction, speech recognition and speech synthesis meet the technical requirements for mine transport vehicles, and shows that the application of voice technology improves the convenience of interaction between drivers and vehicle equipment and the timeliness of warning in dangerous situations.